PARTISIPASI POLITIK PEREMPUAN DAN DISKRIMINASI MEDIA - dewi sucitawathi (Jurnal Ilmiah Dinamika Sosial, 2017)
ABSTRACTThe existence of women is always overshadowed by the domination of men. These conditions have made women always in second position in social life, economy, education and politics. So far we know that the minimum level of women's participation in politics is due to a strong patriarchal culture, but the media plays an important role especially in providing space and opportunities for women to have the same opportunities as men. Media during this time was often made a product news hoax (hoax) against the performance of women politicians. And the media itself sometimes forgets that women's opinions are sometimes needed when taking policy. Discriminatory conditions as mentioned above are not only experienced in our country, but also experienced by several countries around the world. Discriminative acts experienced by Indonesian women one of them interviews that only focused on the ability of men to answer questions, as well as media substance that seemed biased.Keywords: Media Abuse, Stereotype Gender, Impromptu Candidate